Methodology and principles of searching solutions to ensure safe operation of welders in confined spaces - Denis A. Koronchik; Yury I. Bulygin; Dmitry V. Rogozin; Anatoly L. Gaydenko; Alexander N. Legkonogikh (Advanced Engineering Research)
The study aims at finding solutions to ensure the safe operation of welders for hard-to-reach objects in the limited enclosed space with a rapid rise in the content of harmful substances and ambient air temperature. The research subject is the systems of lung protection for welders working under the constrained conditions with high gaseousness and lack or insufficient natural circulation of the ambient air. The research method is a numerical simulation of heat and mass transfer of the harmful substances, welding aerosols, and excess heat under the transient conditions in the three-dimensional formulation. The work methodology is the construction of mathematical models of heat and mass transfer of the contaminants on the basis of the classical gas flue models with their adaptation to the specific boundary conditions, the characteristics of different types of welding in hard-to-reach places including deepwater welding, and taking into account various types of heat transfer. A classification of hard-to-reach objects and types of welding is worked out. It is shown that the resulting mathematical models allow specifying in detail the physical fields of dangerous and harmful factors impact on the welders.